DETERMINANTS OF FISHERMEN INCOME IN REGENCY OF WEST SERAM, MALUKU (Study in 3 Village in West Seram Regency ) - Teddy Christianto Leasiwal (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2017)
Fishing prospects in West Serum regency from year to year more and more promising. It can be seen from the results of fisheries production is increasing. Fish production in 2009 increased by 1,828 tons or 9.5 percent from the previous year, with the potential of fish resources around 592,008.7 tons of new and utilized approximately 2.71 percent. This condition is caused by a lack of such infrastructure is supported by a fishing vessel, which is still dominated by boats and outboard motors around 99 percent. This may reflect that most fishermen in West Serum still relatively fishermen.In an effort to increase the income of fishermen, fishery busineses rurehe (pole And Line) in the District of West rurehe (pole And Line) in the District of West Serum District of West Serum belong in household scale industries (home industry) and the efforts of hereditary existed long ago. Based on the results of research in the field, until now rurehe industrial fisheries (pole and line) has yet to show the maximum results it can be seen from the amount of production obtained are still below the average in the amount of 482.8 tons / year. This condition is a portrait of the ability of the fishermen are still far in producing tuna in the District of West Serum District of West Serum, this is because in addition to lack of knowledge about ways of catching (experience at sea, the low level of education of fishermen, thus affecting the mindset of fishermen in the arrest, as well as the low level of wages of fishermen, lack of technologically which is used also affects tuna arrest method used in this study is a descriptive and quantitative methods. By using Data Analysis panel. The results showed the variables Age does not have an influence on the increase fishermen's income, variable production has a very strong influence on the increase in the income of fishermen. Technology variables also have a strong influence on the increase in revenue.